STUDY OF PHYSICO-CHEMICAL PROPERTIES OF BILE AFTER CHOLECYSTECTOMY ON CHOLELITHIASI S - Ya. M. Vakhrushev; N. A. Khokhlacheva; T. Yu. Maksimova (Архивъ внутренней медицины, 2018)
The aim. To study the physico-chemical properties of hepatic bile and the state of lipid metabolism before and after cholecystectomy for cholelithiasis.Material and methods. 210 patients with stage I cholelithiasis (comparison group) and 90 patients who underwent cholecystectomy for stage II and III of the cholelithiasis (observation group) were examined. The groups were balanced by gender and age. In verification of the diagnosis, in addition to general clinical data, the results of ultrasound examination of the biliary system were used. A duodenal sounding was carried out followed by a macroscopic, microscopic examination of the hepatic portion of bile, determination of its physical properties and chemical composition. Lipid blood metabolism was studied with an estimate of the coefficient of atherogenicity.Results. With ultrasound of the biliary system, signs of biliary sludge were found in 86% of the comparison group patients, in 37% of the patients in the observation group there was an increase in the common bile duct. The study of the chemical composition of the hepatic bile of patients of both groups revealed an increase in cholesterol, total sialic acids and total protein, a decrease in bile acids, phospholipids, cholate-cholesterol and phospholipid-cholesterol coefficients. In the study of physical properties, a thickening of bile and an increase in its viscosity were established. Evaluation of the lipid spectrum of blood revealed that lipid metabolism disorders, which are present in patients with cholecystectomy, are preserved after cholecystectomy.The conclusion. After cholecystectomy for cholelithiasis, bile is still secreted prone to stone formation, as evidenced by its altered physic-chemical parameters. Рatients after cholecystectomy need to use preventive measures to prevent the formation of lithogenic bile.